An ichthyosaur from the UK Triassic–Jurassic boundary: A second specimen of the leptonectid ichthyosaur Wahlisaurus massarae Lomax 2016. (5th February 2018) - Lomax, Dean R.; Evans, Mark; Carpenter, Simon
Abstract : The holotype of Wahlisaurus massarae is known only from a partial skull and postcranial skeleton from the Lower Jurassic, collected near Normanton on Soar, Nottinghamshire, UK. It is diagnosed relative to other ichthyosaurs on the basis of autapomorphies of the coracoid and a unique combination of characters. Here, we report a second specimen of W. massarae . The new specimen comprises a practically complete right coracoid that clearly shows the unique morphology of W. massarae . This specimen was collected in situ from a quarry in Somerset, from the base of the Blue Lias Formation, which corresponds to the Triassic–Jurassic boundary (uppermost Rhaetian or lowermost Hettangian), extending the geographic and stratigraphic range of the species. Furthermore, the coracoid of the new specimen is 20% anteroposteriorly longer than in the holotype, representing a larger individual. In light of preparation and the identification of additional fragments of the holotype, a redescription of the skull morphology of the holotype, as well as comparison with the skull roof of Leptonectes tenuirostris, is included.